2018
DOI: 10.1016/j.foodpol.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Does cooperative membership improve household welfare? Evidence from a panel data analysis of smallholder dairy farmers in Bihar, India

Abstract: The International Food Policy Research Institute (IFPRI), established in 1975, provides evidence-based policy solutions to sustainably end hunger and malnutrition and reduce poverty. The Institute conducts research, communicates results, optimizes partnerships, and builds capacity to ensure sustainable food production, promote healthy food systems, improve markets and trade, transform agriculture, build resilience, and strengthen institutions and governance. Gender is considered in all of the Institute's work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 19 publications
5
94
3
4
Order By: Relevance
“…Similarly being membership in dairy cooperative increases the level of raw milk supply participation by 19.5%. The result is consistent with Phon and Yamaji (2016) and Kumar (2018).…”
Section: Volume Of Milk Size (Sqrtmly)supporting
confidence: 92%
See 1 more Smart Citation
“…Similarly being membership in dairy cooperative increases the level of raw milk supply participation by 19.5%. The result is consistent with Phon and Yamaji (2016) and Kumar (2018).…”
Section: Volume Of Milk Size (Sqrtmly)supporting
confidence: 92%
“…The study conducted by Phon and Yamaji (2016) showed that membership in agricultural cooperatives improves participation decision and intensity in vegetable markets. Similarly, Kumar (2018) indicated dairy cooperative membership has positive impact on milk yield which enhances market participation. Therefore, membership to milk cooperative was hypothesized to affect milk market participation positively.…”
Section: Number Of Cross Breed Milking Cows (Nucrc)mentioning
confidence: 99%
“…On the other hand, these results contrast findings by Ma and Abdulai () and Kumar et al . () for China and India respectively, who found positive and statistically significant relationships between cooperative membership and yields, net farm returns and income. Our results are also in contrast to recent literature suggesting that members of agricultural cooperatives in Cambodia earn greater revenues from vegetable production than non‐members (e.g., Chen et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, to account for both observed and unobserved sources of bias, we employ an endogenous switching regression (ESR) framework to estimate the parameters. The ESR approach addresses this endogeneity problem by estimating the selection and outcome equations simultaneously using the full information maximum likelihood (Lokshin and Sajaia 2004;Ma and Abdulai 2016;Wossen et al 2017;Mishra et al 2018;Kumar et al 2018).…”
Section: Empirical Strategymentioning
confidence: 99%